2016
DOI: 10.1101/041491
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effect of domain growth on spatial correlations

Abstract: Mathematical models describing cell movement and proliferation are important research tools for the understanding of many biological processes. In this work we present methods to include the effects of domain growth on the evolution of spatial correlations between agent locations in a continuum approximation of a one-dimensional lattice-based model of cell motility and proliferation. This is important as the inclusion of spatial correlations in continuum models of cell motility and proliferation without domain… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…This approximation has been previously published [24], and reasonably implies that domain growth 'dilutes' the agent density [16]. Finally, we simplify Eq.…”
Section: Individual Density Functionsmentioning
confidence: 70%
See 1 more Smart Citation
“…This approximation has been previously published [24], and reasonably implies that domain growth 'dilutes' the agent density [16]. Finally, we simplify Eq.…”
Section: Individual Density Functionsmentioning
confidence: 70%
“…To do so we employ an agent-based, discrete random-walk model on a two-dimensional square lattice with volume-exclusion. We have previously shown that the way in which domain growth is implemented in an IBM can alter the population behaviour of agents [16,17]. Therefore, we hypothesised that the way in which domain growth is implemented in a simulation with multiple agent species could change the dominant agent species.…”
Section: Introductionmentioning
confidence: 99%
“…Yates et al (2012) extended these studies and demonstrated that different ways to split the lattice sites ensures that individual-based stochastic simulations provide equivalent results to PDE models on any non-uniformly growing domain. Ross et al (2016Ross et al ( , 2017 investigated different ways to implement domain growth in lattice-based models. They simulated a one-dimensional random walk with volume exclusion, cell proliferation and death.…”
Section: Domain Growthmentioning
confidence: 99%
“…( 4) and (5) as a 'shape' parameter, however, its inclusion in Eqs. ( 4) and ( 5) is not necessary and β can be set to zero 1 A derivation of Eq. ( 1) can be found in the Supplementary material (SM1).…”
Section: I+1 I-1mentioning
confidence: 99%
“…The method we present relies on a separation of variables in a system of equations we construct, and generates a power series weighted by coefficients written in terms of the initial condition. This method was motivated by work conducted on the mathematical modeling of domain growth [1].…”
Section: Introductionmentioning
confidence: 99%